2017
DOI: 10.1186/s40589-017-0053-3
|View full text |Cite
|
Sign up to set email alerts
|

From “selective two-child policy” to universal two-child policy: will the payment crisis of China’s pension system be solved?

Abstract: Background: With the rapid population aging, the payment crisis of China's pension insurance fund is increasing yearly. The government adjusts fertility policy to alleviate population aging and improve the solvency of pension insurance fund. On January 1, 2016, China's fertility policy was adjusted from "selective two-child policy" to universal two-child policy. Methods: This paper establishes actuarial models to analyze how fertility policy adjustment influences the pension insurance fund.Results: (1) if the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 8 publications
1
17
1
Order By: Relevance
“…The projection results indicate that the NRPP would be challenged by an increasing pension payment burden under the one-child policy. The occurrence of the current and accumulated pension deficits would happen in 2030 and 2042, respectively, which is also supported by previous research findings [9,55]. After that, the pension gap would expand yearly at a faster pace.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The projection results indicate that the NRPP would be challenged by an increasing pension payment burden under the one-child policy. The occurrence of the current and accumulated pension deficits would happen in 2030 and 2042, respectively, which is also supported by previous research findings [9,55]. After that, the pension gap would expand yearly at a faster pace.…”
Section: Discussionsupporting
confidence: 86%
“…For example, by developing an overlapping generation model, Coeurdacier et al [32] suggested that relaxing or abandoning fertility restrictions would not offer much help to finance the urban pension system, particularly when children are considered the main source of old-age provision. In addition, Zeng et al [9,33] argued that relaxing population control would relieve the pension burden, but fertility intention plays an essential role which should be improved. Applying a comprehensive risk assessment model, Zhao et al [7] concluded that the urban pension fund would have a gap around 2045, while the accumulated pension deficits would expand to CNY 2270.59 trillion in 2088.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies have considered the fertility policy reform in China. Using actuarial models, Zeng et al [18] demonstrated that the selective two-child policy would delay the pension deficits occurrence by nine years and reduce China's pension gap by 71.85% in 2090. Indeed, according to pension shortage, households would change their behavior at a microeconomic level.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In 2013, China put forward a selective two-child policy that specified that if either the husband or the wife had come from a single-child family, they could have a second child. Three years later, in 2016, another policy change allowed all couples to have a second child (i.e., a universal two-child policy) (Zeng, Zhang, & Liu, 2017). Since the implementation of the two-child policy, China's birth rate has increased (Zhai, Zhang, & Jin, 2014).…”
Section: Introductionmentioning
confidence: 99%